Aplicación de las metodologías de la observación directa e indirecta en el monitoreo del zorro andino (lycalopex culpaeus) para determinar su presencia en los páramos de la parroquia de Toacaso. - Garcés Espinoza, César Alfonso (2022)
The present investigation has the purpose of determining the presence of the Andean fox (Lycalopex culpaeus) in the páramos of the Toacaso parish, Latacunga canton, Cotopaxi Province, through constant monitoring with direct and indirect techniques that will facilitate the search for it. . The study was carried out in the Pilacumbi sector at 3400 masl and the Yugsiche sector at 3600 masl taking into account different geo-positional points in the surroundings in a period of 4 months between the months of April 2022 and August 2022. The Direct monitoring techniques such as linear transects to delimit the study areas and therefore 5 transects were carried out at strategic points in the mentioned places, thus allowing the collection and recording of signs that denote the presence of the species that interests us. Resulting in the sighting of both direct and indirect signs of the Andean fox. Obtaining with this a total of 50 signs between excreta, footprints and beds/burrows at altitudes from 3400 masl to 3660 masl which, according to the literature, is sufficient to determine the fixed presence of this animal in the Toacaso sector. In turn, the presence of feral canids that were witnessed by the resident population in these places was determined, which is considered one of the factors that limits the habitat of Lycalopex culpaeus.